Training and Developing an Entrepreneurial Spirit Through Creative Economy in the Islamic Boarding School Environment - Mubarok, Muhammad; Susyanti, Jeni; Nurhidayah, Nurhidayah (FKIP - Universitas Riau, 2025)
Cottage Darul Ulum Al- Fadholi Islamic Boarding School is one of from that's all cottage Islamic boarding school students in Malang. pondok Islamic boarding school This must Can utilise digitalization is developing very rapidly with develop soul entrepreneurship in form economy creative For students in the environment Cottage Darul Ulum Al- Fadholi Islamic boarding school. In the management and development cottage this, there is very supportive business activity cottage that is business economy creative empowerment his students. Research This have objective For Can develop and improve soul entrepreneurship through economy creative pad santi in the environment Cottage Darul Ulum Al- Fadholi Islamic boarding school. The methods used is descriptive with technique observation, companion, and evaluation. The results of study This show that Darul Ulum Al- Fadholi Islamic Boarding School in Malang is carrying out economy creative For grow soul entrepreneurship with develop craft hand simple made by guardian students and sold as a souvenir. Students who are interested can entrepreneurship in video, film, photography, and video production industries. They are also involved in writing scripts, dubbing, film, and photography. Food and beverage industry need Keep going develop product they in accordance with need students, with planning and management mature finance and marketing.